1983
DOI: 10.1007/bf00006045
|View full text |Cite
|
Sign up to set email alerts
|

Nematodes from river drift and surface drinking water supplies in southern Ontario

Abstract: Sixty-six genera'of nematodes representing 37 families were collected over a 13-month period from untreated and treated water from three water treatment plants in southern Ontario. Two plants receive water from the Grand River which drains agricultural, residential and industrial regions, the third from a small stream in an agricultural district. Specimens were isolated by filtration from weekly samples of untreated and treated water, most were identified to genus but a few to species.Estimated mean density in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…As in the Krähenbach (Beier & Traunspurger, 2003b), the Adige (Andrássy, 1959), the Danube (Andrássy, 1962) and the Grand River (Mott & Harrison, 1983), the nematode population of the Körsch shows a high percentage of females and juveniles and a low percentage of males. The low percentage of males in all these systems can have no signi cant impact on reproductive output since most of the lotic nematodes reproduce parthenogenetically.…”
Section: Age Structurementioning
confidence: 95%
“…As in the Krähenbach (Beier & Traunspurger, 2003b), the Adige (Andrássy, 1959), the Danube (Andrássy, 1962) and the Grand River (Mott & Harrison, 1983), the nematode population of the Körsch shows a high percentage of females and juveniles and a low percentage of males. The low percentage of males in all these systems can have no signi cant impact on reproductive output since most of the lotic nematodes reproduce parthenogenetically.…”
Section: Age Structurementioning
confidence: 95%
“…It has been frequently suggested that meiofauna depend on external forces to become suspended in the water column and carried to distant habitats (Hagerman & Rieger, 1981;Mott & Harrison, 1983;Fleeger et al, 1984;Fegley, 1985;Armonies, 1988;Palmer, 1988;Bertelsen, 1998;Powers, 1998). One would thus expect to encounter more meiofauna in the water column of high-energy environments than of more protected ones.…”
Section: Exposed Versus Protectedmentioning
confidence: 98%
“…Although nematodes have been collected from plankton samples (Hagerman & Rieger, 1981;Sibert, 1981) and marine snow (Shanks & Walters, 1997), they are poor swimmers (Fegley, 1985) and likely become suspended in the water column via external forces (water currents or bioturbation), as is assumed for most meiofaunal taxa (Hagerman & Rieger, 1981;Mott & Harrison, 1983;Fleeger et al, 1984;Fegley, 1985;Armonies, 1988;Palmer, 1988;Bertelsen, 1998;Powers, 1998;Fonseca-Genevois et al, 2006). Many harpacticoid copepods, however, are much better active dispersers than nematodes (Widbom, 1983;Ó lafsson & Moore, 1990Ó lafsson & Moore, , 1992 and occasionally enter the water column under their own power (Alldredge & King, 1980, 1985Bell et al, 1988;Kurdziel & Bell, 1992;Walters and Bell, 1994;Teasdale et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Most adult forms are about 1 mm long (Nicholas, 1975;Croll, 1977). Nematodes found in untreated drinking waters originate from animals drifting into the water distribution system (Mott and Harrison, 1983). In treated drinking water, the source of nematodes is likely to be either drifting or colonization and breeding within the water treatment plant (Cobb, 1918;George, 1966;Tombes et al, 1979).…”
Section: Discussionmentioning
confidence: 99%